Targeting the MDK/c‐Myc complex to overcome temozolomide resistance in glioma - Xiaonan Xi; Xiaojing Ding; Qianqian Wang; Ning Liu; Bangmao Wang; Genbei Wang; Weilong Zhong; Yaxin Lu (Clinical and Translational Medicine, 2025)
Abstract Background Temozolomide (TMZ), which is an alkylating agent, is the standard chemotherapeutic drug used for glioma treatment. However, the development of resistance to TMZ limits its efficacy. Thus, identifying novel therapeutic targets is necessary. Methods In this study, the levels of midkine (MDK) and c‐Myc expression in glioma patient samples downloaded from TCGA were analyzed. Their interactions were also demonstrated through microthermometry and immunocoprecipitation. Furthermore, proteomics technology and Western blot showed that MDK interacted with c‐Myc and influenced its ubiquitination, thereby activating a prosurvival signalling pathway and epithelial–mesenchymal transition mechanism, which contributed to TMZ resistance. To target the MDK/c‐Myc complex, we screened for a small‐molecule inhibitor (ACT001) that specifically disrupts the interaction between MDK and c‐Myc. Treatment with ACT001 greatly sensitized TMZ‐resistant glioma cells to TMZ, promoting cell death and inhibiting cell proliferation. Moreover, combination therapy with ACT001 and TMZ showed synergistic effects that inhibit tumour growth in glioma xenograft models and glioma in situ models. Results ACT001 facilitated the degradation of c‐Myc by focusing on the MDK/c‐Myc complex and controlled the Wnt/β‐catenin signalling pathway via MDK, ultimately halting the advancement of glioma. When combined with TMZ, ACT001 showed good therapeutic potential for the treatment of glioma. Conclusion Focusing on the MDK/c‐Myc complex could be an effective approach to combat resistance to TMZ in glioma. Therapy with ACT001 may be a novel approach to improve the efficacy of TMZ‐based chemotherapy in patients with glioma. Further preclinical and clinical studies are warranted to validate the therapeutic potential of targeting the MDK/c‐Myc complex in glioma treatment.